Müslüman feminizmi : Fatima Mernissi örneği - Mouas, Jahar (My University, 2022)
Feminizm, aslında, çeşitli görüntüler altında, kadın özgürlüğü konusunda insanlık tarihi boyunca var olmuş eleştirel düşüncenin modern dönemdeki ifadesidir. Bahusus Fransız İhtilali ardından gelen dönemde görünür olan serbestlikçi ve devrimci düşüncelerin ilerlerdiği yıllarda ve sosyal normların artık kabul görmemeye başlandığı zamanda ortaya çıkan feminizm, her iki cinsiyetin de yaşamdan gelen eşitliklerinin sosyal yaşam ve iş yaşamı gibi pek çok alanda sağlanması gayesiyle ortaya atılmıştır. Bu doğrultuda, feminizm akımı zaman içinde birçok politikaya önayak olmuştur. Bu düşüncenin yayıldığı ülkerde feminizmin meydana getirdiği psikolojik ve toplumsal değişimleri açık biçimde gözlemleyebiliyoruz. Müslüman aktörlerde gözlemlenen feminizm de özellikle 1990’lı yıllardan sonra çok daha baskın biçimde hissedilmeye başlanmıştır. Feminizm dalgası, Müslüman kadın bağlamında, özellikle din-ataerkillik ve İslam’ın kadın algısı üzerinde çeşitli tartımalara sebep olmutur. Bu araştırmanın amacı Müslüman feminizmini Faslı feminist Fatima Mernisi örneği üzerinden tasvir etmek ve anlamaktır. Çalışmamızda bilimsel araştırma yöntemlerinden nitel araştırma yöntemi kullanılmıştır. Özellikle dokümantasyon ve içerik analizi tekniklerinden istifade edilmiştir. Çalışmanın sonucunda Mernissi’nin feminist okumaları doğrultusunda Müslüman kadına yönelik cinsiyet ayrımcılığının temelinde İslamiyet değil; genel anlamda dine sonradan eklenen yorumlar olduğu sonucu ortaya çıkmıştır.

Feminism is one of the currents of thought that has existed in human history and is strongly defended in today's world. This trend, which emerged during the developmental periods of libertarian and revolutionary ideas that emerged especially in the post-French Revolution period and when social norms were now being questioned, was put forward in order to ensure the equality of women and men in society, education, work and many more areas. In this context, feminism has spawned many different factions over time. It would not be wrong to say that this idea has undergone changes by fusing with sociological and religious factors in different countries and geographical regions. Since the 1990s, Islamic Feminism has started to be spoken more loudly, especially in the Islamic Geography and in Europe. This current of ideas emerged as a reaction against the idea that patriarchy, which was more accepted from the beginning of the emergence of feminism, stems from religion and the idea that Islam saw women as a second class citizen. The wave of feminism has led to various debates in the context of Muslim women, especially on religion-patriarchy and the perception of women in Islam. The aim of the research is to describe and understand Muslim feminism through analyzing the case of the Moroccan feminist Fatima Mernisi. During this study Qualitative research method was used, In particular, documentation and content analysis techniques were used. In the light of the data obtained, as a result of the study, it has been revealed that the main fact underlying the gender discrimination against Muslim women in line with Mernissi's feminist readings is not the religion of Islam, but the interpretations added to the religion in general.
Keywords: Fas; Fatima Mernissi; Fatima Mernissi Feminism; Feminism; Feminizm; Islam; İslam; Morocco; Muslim Feminism; Müslüman Feminizmi